Sensory and instrumental evaluation of alcoholic beverages - Heymann, Hildegarde; Ebeler, Susan E. (Elsevier, 2017)
"Sensory and Instrumental Evaluation of Alcoholic Beverages introduces the value of sensory analysis to the alcoholic beverage industry through the detailed lens of sensory analysis techniques. From traditional methods, to the most modern rapid methods, this book presents comprehensive insights and applications"--Provided by publisher.